Classical NF-κB Metabolically Reprograms Sarcoma Cells Through Regulation of Hexokinase 2 - Londhe, Priya; Yu, Peter Y.; Ijiri, Yuichi; Ladner, Katherine J.; Fenger, Joelle M.; London, Cheryl; Houghton, Peter J.; Guttridge, Denis C. (Frontiers in Oncology, 2018)
Background Metabolic reprogramming has emerged as a cancer hallmark, and one of the well-known cancer-associated metabolic alterations is the increase in the rate of glycolysis. Recent reports have shown that both the classical and alternative signaling pathways of nuclear factor κB (NF-κB) play important roles in controlling the metabolic profiles of normal cells and cancer cells. However, how these signaling pathways affect the metabolism of sarcomas, specifically rhabdomyosarcoma (RMS) and osteosarcoma (OS), has not been characterized. Methods Classical NF-κB activity was inhibited through overexpression of the IκBα super repressor of NF-κB in RMS and OS cells. Global gene expression analysis was performed using Affymetrix GeneChip Human Transcriptome Array 2.0, and data were interpreted using gene set enrichment analysis. Seahorse Bioscience XFe24 was used to analyze oxygen consumption rate as a measure of aerobic respiration. Results Inhibition of classical NF-κB activity in sarcoma cell lines restored alternative signaling as well as an increased oxidative respiratory metabolic phenotype in vitro. In addition, microarray analysis indicated that inhibition of NF-κB in sarcoma cells reduced glycolysis. We showed that a glycolytic gene, hexokinase (HK) 2, is a direct NF-κB transcriptional target. Knockdown of HK2 shifted the metabolic profile in sarcoma cells away from aerobic glycolysis, and re-expression of HK2 rescued the metabolic shift induced by inhibition of NF-κB activity in OS cells. Conclusion These findings suggest that classical signaling of NF-κB plays a crucial role in the metabolic profile of pediatric sarcomas potentially through the regulation of HK2.